A Review of Factors Influencing Postpartum Hemorrhage: Age, Parity, Pregnancy Spacing, Anemia, Newborn Weight, Prolonged Labor, Perineal Tear, and Type of Labor - Nana Usnawati; Astin Nur Hanifah (Knowledge Dynamics, 2024)
Postpartum hemorrhage is one of the most common causes of maternal mortality worldwide. One of the main causes of maternal mortality is bleeding, it is estimated that around 70% of maternal mortality are caused by postpartum hemorrhage. According to data from the Indonesian Ministry of Health in 2022 the number of maternal mortalities in East Java was 499 deaths, the causes of which were found in hypertensive disorders of pregnancy (24.45%) and bleeding (21.24%). The purpose of this systematic literature review is to summarize and examine the literature related to risk factors that affect postpartum hemorrhage. The framework used was PICOC with a population of laboring mothers who experienced postpartum hemorrhage. Systematic literature review using 1 data source, namely google scholar with 169 articles and filtering articles and critical appraisal so that 6 articles were reviewed. The 6 articles showed that age, parity, gestational distance, birth weight, prolonged parturition, perineal tear and type of delivery were associated with the incidence of postpartum hemorrhage. It is recommended to increase education about healthy reproductive age, regulate the number of parity and maintain pregnancy distance, early detection of anemia, administration of 90 FE tablets during pregnancy, early detection of risk factors for postpartum hemorrhage, and delivery planning and prevention of complications.